Application of the Flipped Classroom Model Using Games-Based Learning Multimedia in Increasing Students’ Learning Outcomes - Bayu Pradikto; Sofino Sofino (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the low students’ learning outcomes and students’ satisfaction, which continues to decline. In contrast, distance and face-to-face learning are limited to non-formal education learning technology courses. The study aimed to improve learning in the Non-Formal Education Learning Technology course in the S1 Non-Formal Education Study Program by implementing games-based learning multimedia with the flipped classroom model. The research was conducted on 30 students in semester III/A. By applying the flipped classroom model, the research was conducted in the classroom and at each student's home. The research used a Pre-Experimental Design with a One-Group Pretest-Posttest Design. The data collection technique was carried out by testing. The pre-test was carried out to collect data on students' initial abilities, while the post-test was carried out to test the effect of the treatment. The study used three statistical tests, namely (1) normality, (2) homogeneity, and (3) hypothesis testing. The results indicate that the control class sample data were normally distributed. After treatment, initial data on students' abilities are interpreted as normal or homogeneous. The results of hypothesis testing show that there is a significant effect of flipped classrooms based on game multimedia in non-formal education learning technology courses with an average value of the experimental class at 81.63.